1992
DOI: 10.1142/s0218127492000446
|View full text |Cite
|
Sign up to set email alerts
|

Riddled Basins

Abstract: Theory and examples of attractors with basins which are of positive measure, but contain no open sets, are developed; such basins are called riddled. A theorem is established which states that riddled basins are detected by normal Lyapunov exponents. Several examples, both mathematically rigorous and numerical, motivated by applications in the literature, are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
330
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 411 publications
(347 citation statements)
references
References 0 publications
3
330
0
4
Order By: Relevance
“…The description of riddled basins was introduced in Ref. [90] where it was shown that for certain class of dynamical systems with an invariant subspace: (i) if there is a chaotic attractor in the invariant subspace; (ii) if there is another attractor in the phase space; and (iii) if the Lyapunov exponent transverse to the subspace is negative, then the basin of the chaotic attractor in the invariant subspace can be riddled with holes belonging to the basin of the other attractor. That is, for every initial condition that asymptotes to the chaotic attractor in the invariant subspace, there are initial conditions arbitrarily nearby that asymptote to the other attractor.…”
Section: Example 2: Controlling Riddled Basinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The description of riddled basins was introduced in Ref. [90] where it was shown that for certain class of dynamical systems with an invariant subspace: (i) if there is a chaotic attractor in the invariant subspace; (ii) if there is another attractor in the phase space; and (iii) if the Lyapunov exponent transverse to the subspace is negative, then the basin of the chaotic attractor in the invariant subspace can be riddled with holes belonging to the basin of the other attractor. That is, for every initial condition that asymptotes to the chaotic attractor in the invariant subspace, there are initial conditions arbitrarily nearby that asymptote to the other attractor.…”
Section: Example 2: Controlling Riddled Basinsmentioning
confidence: 99%
“…Rigorous results on the dynamics of riddled basins for discrete maps were presented in Refs. [90,91]. The dynamics of riddled basins was subsequently investigated in [92] using a more realistic physical model.…”
Section: Example 2: Controlling Riddled Basinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in Section 4 we apply this procedure to a specific example: the quadratic map with a particular parameter value studied previously by Ruelle [15]. In particular, we estimate a time average for this map which can be shown to be a Lyapunov exponent for a two-dimensional map studied in [2,1]. In the latter paper it is vital to know rigorously that the Lyapunov exponent is negative.…”
Section: The Mapmentioning
confidence: 99%
“…One exponent will simply be the Lyapunov exponent of the one-dimensional map, and the other will reflect the rate of contraction or expansion transverse to A for the two-dimensional map. This planar map, originally studied in [12], has been of great interest recently as a fundamental example of the phenomenon of "riddled" and "intermingled" basins of attraction [2,1]. In order to verify mathematically the properties of this map which were discovered with a computer, it is necessary to verify that the "transverse" Lyapunov exponent for A is negative, which in particular implies that A attracts a set of positive Lebesgue dimensional measure.…”
Section: Lyapunov Exponentsmentioning
confidence: 99%